2019
DOI: 10.1302/0301-620x.101b11.bjj-2018-1447.r2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo wear measurement in a modern total knee arthroplasty with model-based radiostereometric analysis

Abstract: Aims A retrospective study was conducted to measure short-term in vivo linear and volumetric wear of polyethylene (PE) inserts in 101 total knee arthroplasty (TKA) patients using model-based radiostereometric analysis (MBRSA). Patients and Methods Nonweightbearing supine RSA exams were performed postoperatively and at six, 12, and 24 months. Weightbearing standing RSA exams were performed on select patients at 12 and 24 months. Wear was measured both linearly (joint space) and volumetrically (digital model ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…This observation is in line with an earlier study that also showed that most wear occurs on the medial side. 30 The lateral wear for both insert groups is negative. This 'negative' wear is most likely explained by movement of the Table IV.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This observation is in line with an earlier study that also showed that most wear occurs on the medial side. 30 The lateral wear for both insert groups is negative. This 'negative' wear is most likely explained by movement of the Table IV.…”
Section: Discussionmentioning
confidence: 95%
“…This observation is in line with an earlier study that also showed that most wear occurs on the medial side. 30…”
Section: Discussionmentioning
confidence: 99%
“…Classical marker-based RSA or mbRSA approach offers the opportunities: to measure in vivo implant fixation [43,44], to investigate, e.g., new THA design or coatings, degenerative changes [45][46][47], joint kinematics [48] and pathomechanism [49], and bony fusion [50]. Additionally, it offers the opportunity to investigate the effect of joint material connection within total joint arthroplasty, likewise the head-taper junction [17].…”
Section: Discussionmentioning
confidence: 99%
“…4,21,28 Other potential applications of RSA include in vivo linear and volumetric wear using model-based radiostereometric analysis. [29][30][31][32][33] Gascoyne et al 30 used modelbased RSA to evaluate linear and volumetric polyethylene (PE) wear in 101 TKA patients. Consecutive, precise measurements of joint space distance in supine and weightbearing positions were used as a surrogate for determining linear polyethylene (PE) wear, while volumetric wear was measured following the introduction of the computer-aided design (CAD) model and assessment of the degree of overlap between the PE component and femoral condyles.…”
mentioning
confidence: 99%
“…Consecutive, precise measurements of joint space distance in supine and weightbearing positions were used as a surrogate for determining linear polyethylene (PE) wear, while volumetric wear was measured following the introduction of the computer-aided design (CAD) model and assessment of the degree of overlap between the PE component and femoral condyles. 30 Similarly, RSA was used in another study to measure the in vivo wear of different bearing types of the Oxford unicompartmental knee replacement. The linear distance between the tibial tray and femoral prosthesis was calculated and subtracted from the estimated bearing thickness.…”
mentioning
confidence: 99%